Polygenic risk for schizophrenia and schizotypal traits in non-clinical subjects - Nenadić, Igor; Meller, Tina; Schmitt, Simon; Stein, Frederike; Brosch, Katharina; Mosebach, Johannes; Ettinger, Ulrich; Grant, Phillip; Meinert, Susanne; Opel, Nils; Lemke, Hannah; Fingas, Stella; et al. (Psychological medicine, 2022)
Schizotypy is a putative risk phenotype for psychosis liability, but the overlap of its genetic architecture with schizophrenia is poorly understood. We tested the hypothesis that dimensions of schizotypy (assessed with the SPQ-B) are associated with a polygenic risk score (PRS) for schizophrenia in a sample of 623 psychiatrically healthy, non-clinical subjects from the FOR2107 multi-centre study and a second sample of 1133 blood donors. We did not find correlations of schizophrenia PRS with either overall SPQ or specific dimension scores, nor with adjusted schizotypy scores derived from the SPQ (addressing inter-scale variance). Also, PRS for affective disorders (bipolar disorder and major depression) were not significantly associated with schizotypy. This important negative finding demonstrates that despite the hypothesised continuum of schizotypy and schizophrenia, schizotypy might share less genetic risk with schizophrenia than previously assumed (and possibly less compared to psychotic-like experiences).